2011
DOI: 10.1111/j.1445-2197.2010.05641.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of osteoradionecrosis of the temporal bone

Abstract: The incidence of osteoradionecrosis of the temporal bone was 8.5% (95% confidence interval = 3.6-13.4%). Osteoradionecrosis of the temporal bone can present in excess of 10 years after treatment completion. This result may actually under -represent the true incidence of the complication. It has significant morbidity associated with its development and, occasionally, mortality. Those people undergoing radiotherapy to the parotid region may be at higher risk of osteoradionecrosis. A new classification system for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Temporal bone ORN was first documented in 1952 by Block et al . It is reported to affect 8.5% of patients receiving radiation near the temporal bone within 10 years. More recently, there are a growing number of case reports and case series documenting TB‐ORN.…”
Section: Temporal Bone Ornmentioning
confidence: 99%
“…Temporal bone ORN was first documented in 1952 by Block et al . It is reported to affect 8.5% of patients receiving radiation near the temporal bone within 10 years. More recently, there are a growing number of case reports and case series documenting TB‐ORN.…”
Section: Temporal Bone Ornmentioning
confidence: 99%
“…ORN is a severe, late complication of head and neck radiation affecting 5% to 22% of patients and most commonly involves the mandible . A recent report demonstrated that 8.5% of patients receiving radiation near the temporal bone developed ORN of the temporal bone within 10 years of radiotherapy . Increased risk of ORN is associated with factors such as bone proximity to tumor/treatment site, presence of dental disease (for mandibular ORN), and increased radiation dose .…”
Section: Discussionmentioning
confidence: 99%
“…Many of these patients were managed surgically, including mastoidectomy and petrosectomy in order to remove as much of the dead bone as possible. 7,13 …”
Section: Discussionmentioning
confidence: 99%
“…Despite an incidence of up to 12.5% in a recent study of patients receiving postoperative radiotherapy for parotid tumors and 8.5% in another cohort who had undergone postoperative radiotherapy to the temporal bone for a variety of head and neck cancers, no large case series describing the computed tomography scan (CT) findings of temporal bone osteoradionecrosis (TB-ORN) exists 12,13 . We feel it is important for the radiologist to be aware of these findings when evaluating patients with a history of radiation therapy to the head and neck that present with new clinical findings.…”
Section: Background and Purposementioning
confidence: 99%